The influence of attribute importance and interpersonal influence on consumer repurchase intention between high and low involvement products / Oriah binti Haji Akir - Haji Akir, Oriah (2015)
This research has established the linkages between attribute importance variables and interpersonal influence variables on repurchase intention using high and low involvement products as a comparison. Meanwhile consumer prior product knowledge was hypothesised as the moderating variable between attribute importance variables and interpersonal influence variables on repurchase intention. This research was conducted using cross-sectional survey method design and the units of analysis were intercepted at mall exit point. Since this research was theoretical and fundamental in nature, a non-probability sampling and quota sampling technique was employed. Kuching City, a state capital of Sarawak, Malaysia was the chosen location to test the research conceptual framework due to its diversity in terms of racial composition and culture. Kuching City is one of the largest city in Malaysia, besides Kuala Lumpur, Johor and Penang. Albeit only one small city, Kuching does not only represents Malaysia’s unique cultural and multiracial characteristics but also represents the behaviour of consumers in the Asian and South East Asian regions. The findings of this research revealed mixed results. It was indicated that attribute importance variables and interpersonal influence variables predict consumer repurchase intention for high involvement products stronger than that of low involvement products for certain product categories. However, the valence of consumer prior product knowledge in moderating the relationship between these two sets of variables was not very conclusive. The research presented three contributions to the extension of new knowledge in relation to consumer buying behaviour. These contributions were in terms of theory, methodology and practice. The research also provided additional implications insights which are beneficial for marketers and managers to streamline their marketing plan and strategies in order to sustain in the market place and win the mind and heart of the consumers at large.